Pengaruh Tingkat Kemandirian Belajar Siswa Terhadap Hasil Belajar Matematika - Amran; Lian G. Otaya; Ingka Rizkyani Akolo (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
The lack of independence and self-confidence makes it difficult for students to understand mathematics. Independent learning is expected to enhance students' initiative and comprehension more effectively. This study aims to analyze the effect of students’ learning independence on their mathematics learning outcomes at SDN 2 Tilango. This is a quantitative study, with the population and sample consisting of 35 fourth and fifth-grade students at SDN 2 Tilango. The research instrument was a questionnaire validated by experts. Data analysis included tests of validity, reliability, normality, homogeneity, and simple linear regression. The results showed that learning independence had a very positive and significant effect on mathematics learning outcomes, with a correlation coefficient of 0.923 and an R Square value of 0.852. Although some students are still influenced by social factors, overall learning independence is categorized as good to excellent, and thus needs to be continuously fostered through active roles of teachers and parents.